Assembly and Covalent Cross-Linking of an Amine-Functionalised Metal-Organic Cage - Schneider, Matthew L.; Markwell-Heys, Adrian W.; Linder-Patton, Oliver M.; Bloch, Witold M. (Frontiers in Chemistry, 2021)
The incorporation of reactive functional groups onto the exterior of metal-organic cages (MOCs) opens up new opportunities to link their well-defined scaffolds into functional porous solids. Amine moieties offer access to a rich catalogue of covalent chemistry; however, they also tend to coordinate undesirably and interfere with MOC formation, particular in the case of Cu2 paddlewheel-based MOCs. We demonstrate that tuning the basicity of an aniline-functionalized ligand enables the self-assembly of a soluble, amine-functionalized Cu4L4 lantern cage (1). Importantly, we show control over the coordinative propensity of the exterior amine of the ligand, which enables us to isolate a crystalline, two-dimensional metal-organic framework composed entirely of MOC units (2). Furthermore, we show that the nucleophilicity of the exterior amine of 1 can be accessed in solution to generate a cross-linked cage polymer (3) via imine condensation.